Mechanisms of action of caffeine in a non-fatigued state and during fatiguing exercise : responders versus non-responders - Mesquita, Ricardo N. O. (2017)
Several studies have documented the ergogenic effects of caffeine, but its mechanisms of action are not fully understood yet. The purpose of this study was to investigate the underlying mechanisms that may explain any caffeine-induced effects in a non-fatigued state and during exhaustive stretch-shortening cycle exercise (SSC). Eighteen males participated in this randomised, double-blind, placebo-controlled crossover trial. Baseline measures of plantarflexion force, drop jump, squat jump, voluntary activation, neuromuscular transmission, contractile properties, H-reflex, corticospinal excitability, short-intracortical inhibition, intracortical facilitation (ICF), corticospinal silent period (CSP) and blood biomarkers were made before administration of caffeine (6 mg•kg-1 ) or placebo. After a 1-hour rest, participants repeated the baseline measures, followed by a fatigue protocol that consisted of SSC exercise until exhaustion on a sledge apparatus by repeating series of 40 bilateral rebound jumps, with resting periods of 3 min. Neuromuscular testing was carried out throughout and after the fatigue protocol. Caffeine enhanced pre to postcapsule drop jump height, decreased CSP, suppressed a time-related decrease in ICF and mobilized free fatty acids. At the group level, caffeine did not alter the number of sets completed. However, ten responders were identified and pre to postcapsule changes in inhibitory mechanisms were significantly correlated with the number of sets completed in the caffeine trial. Responders also benefited from a decreased sense of effort during exercise and from an accelerated recovery of neuromuscular transmission failure after fatigue. The observed effects of this drug on the neuromuscular system may be explained by the reversal of inhibitory effects of adenosine. Effects of caffeine are highly dependent on individual responsiveness and thus, examination of its effects on an individual basis is highly recommended.